Formation of potassium solubilising biofertilizers using pea pod powder - GANGULY, MUKUR (Indian Phytopathology, 2016)
Biofertilizers are group of microorganisms which are known to enhance the plant growth by different mechanisms like nitrogen fixation, mineral solubilisation etc, which also help in reducing environmental pollution caused by the chemical fertilizers. The main objective of this study was to develop a cost effective and simple method to produce biofertilizers using pea pods which is a.common kitchen waste.This kitchen waste was used to prepare biofertilizer using solid substrate fermentation.This was then applied on Wheat (Triticum aestivum) and Turkish gram (Vigna aconitifolia) to check the growth response with respect to root length, shoot length and no of leaves. The results of the experiment showed that plant samples treated pea pod powder showed enhanced growth response as compared to the controls in both solid (along with a carrier) as well as liquid biofertilizer(direct application) treatment.